Judicial Overreach in Constitutional Court Decisions: Navigating the Boundary Between Constitutional Interpretation and Judicially Created Legislation - Kurdi, Kurdi; Joko Cahyono; Teuku Ahmad Dadek (Jurnal Ilmu Hukum Kyadiren, 2026)
The imbalance between the Constitutional Court’s prescribed authority and its growing tendency to expand its judicial function has raised significant concerns regarding judicial overreach in Indonesia’s constitutional system. This study seeks to identify the defining characteristics of judicial overreach and to delineate the boundaries between legitimate constitutional interpretation and covert judicial lawmaking. It further evaluates the implications of this phenomenon for democratic legitimacy, public trust, and adherence to the separation-of-powers principle. Employing normative legal research methods, this study utilizes statutory, conceptual, and case-law analyses with a particular focus on Constitutional Court Decision No. 90/PUU-XXI/2023. The findings reveal a shift in the Constitutional Court’s role from a negative legislator to a positive legislator, evidenced by expanded interpretations unsupported by constitutional text and inconsistencies with established precedents. These developments have undermined public confidence and contributed to increasing constitutional uncertainty. The study concludes that stricter limitations on the Court’s interpretive discretion and enhanced judicial accountability are essential to preserving the integrity of constitutional review within Indonesia’s democratic framework.